Family law and bankruptcy - Fary, Peter (Chatswood, NSW : LexisNexis, 2024)
"Family Law and Bankruptcy is a comprehensive guide designed to unpack the intersection between family law and bankruptcy. This book is a must have for practitioners in who practice in the areas of family law and bankruptcy, as well as for insolvency practitioners who want to understand this often-complex intersection. Features: a unique, accessible and comprehensive guide to the intersection of bankruptcy and family law matters; authored by a leading practitioner in the area; update to date commentary on cases and legislation."--Publisher's website.
Includes bibliographical references and index.
Mode of access : Available online.
Keywords: Bankruptcy -- Law and legislation -- Australia; Divorce -- Law and legislation -- Australia; Domestic relations -- Australia; Law; Electronic books